Evaluation of Software Quality to Improve Application Performance Using Mc Call Model - Inda D Lestantri; Rosini Rosini (Universitas Airlangga, 2018)
The existence of software should have more value to improve the performance of the organization in addition to having the primary function to automate. Before being implemented in an operational environment, software must pass the test gradually to ensure that the software is functioning properly, meeting user needs and providing convenience for users to use it. This test is performed on a web-based application, by taking a test case in an e-SAP application. E-SAP is an application used to monitor teaching and learning activities used by a university in Jakarta. To measure software quality, testing can be done on users randomly. The user samples selected in this test are users with an age range of 18 years old up to 25 years, background information technology. This test was conducted on 30 respondents. This test is done by using Mc Call model. Model of testing Mc Call consists of 11 dimensions are grouped into 3 categories. This paper describes the testing with reference to the category of product operation, which includes 5 dimensions. The dimensions of testing performed include the dimensions of correctness, usability, efficiency, reliability, and integrity. This paper discusses testing on each dimension to measure software quality as an effort to improve performance. The result of research is e-SAP application has good quality with product operation value equal to 85.09%. This indicates that the e-SAP application has a great quality, so this application deserves to be examined in the next stage on the operational environment.